Dose tapering for ciclosporin in cats with nonflea‐induced hypersensitivity dermatitis. Issue 3 (27th March 2013) - Steffan, Jean; Roberts, Elizabeth; Cannon, Andrea; Prélaud, Pascal; Forsythe, Peter; Fontaine, Jacques; King, Stephen; Seewald, Wolfgang
Abstract : Background: Little information is available on the ciclosporin dose‐tapering regimen and clinical response in the treatment of feline hypersensitivity dermatitis. Hypothesis/Objectives: To test a dose‐tapering regimen and assess efficacy and clinical safety for up to 18 weeks. Animals: Eighty‐eight client‐owned cats with feline hypersensitivity dermatitis. Methods: Cats that received either a placebo or ciclosporin at 2.5 mg/kg or 7 mg/kg daily for 6 weeks were given 7 mg/kg ciclosporin daily for 4 weeks. Depending on the clinical response, the dose was tapered from daily to every other day over the next 4 weeks and further to twice a week for an additional 4 weeks. Results: After all cats received 7 mg/kg for 4 weeks, the dose could be tapered to every other day for the next 4 weeks in 70% of cats remaining in the study. During the next 4 weeks, 57, 15 and 22% of cats remaining in the study could be treated at twice a week, every other day or daily, respectively. After the first 4 weeks, the mean lesion score and owner‐assessed pruritus improved over baseline by 69 and 61%, respectively, and remained stable during the following 8 weeks. Approximately 65% of the cats in the study were reported to have an adverse event (AE), very often mild and resolving spontaneously. The most frequent AEs were gastrointestinal and included primarily vomiting and diarrhoea. Eighty per cent of AEs occurred when cats were on daily treatment. Conclusions and clinical importance: Results suggest that the induction dose of 7 mg/kg ciclosporin can be tapered as soon as 4 weeks without deterioration of the clinical response. Establishment of the lowest effective dosing regimen of ciclosporin reduced the frequency of AEs.